(untitled) - Hayami, Yujiro (Baltimore, 1985)
Contents: I. Problems and theory; II. International comparisions; III. Agricultural growth in the united states and japan;... .
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Economic aspects